A comprehensive survey analysis focusing on the effect of living literacy on residential environment and health recognition under COVID‐19 in Japan. (24th October 2022) - Kawasaki, Takashi; Kikuta, Koki; Hayashi, Motoya; Bando, Michiko; Hasegawa, Kenichi; Sawachi, Takao
Abstract: Appropriate knowledge and actions of residents in housing are expected to reduce health effects, defined as "living literacy." With the spread of COVID‐19 and the diversification of lifestyles, a quantitative evaluation of a comprehensive model that includes living literacy in the housing environment is required. In this study, the author conducted two web‐based surveys of approximately 2000 different households in Japan during the summer of 2020 and winter of 2021, and a statistical analysis based on the survey results. As a result, ventilation by opening windows was observed as a new resident behavior trend under COVID‐19. In addition, structural equation modeling using the survey samples confirmed the certain relationship between living literacy and subjective evaluation of the indoor environment and health effects in both periods.